Performance Optimization of Air Cooler Using Peltier and SEPIC Converter as Temperature Control - Muchammad Ruben Imawan; Rachma Prilian Eviningsih; Novie Ayub Windarko (Universitas Muhammadiyah Surakarta, 2025)
Air cooler has an evaporative mode that is used to get a cooler temperature output than without using evaporative mode. The evaporative cooling process involves water that is cooled with an ice cube placed in a water tank on the air cooler, where the outside air entering the air cooler will be cooler when exposed to honeycomb that has been submerged in cold water from the water tank so that the air temperature released by the air cooler will be cooler. The process of cooling the air temperature of the air cooler uses an ice cube which when used for a long time, the temperature will start to rise again so that the air coming out of the air cooler will rise again and become less cold than before. The purpose of this research is to create a system to keep the water temperature in the air cooler tank stable so that the temperature of the air released will also be cooler. This research was conducted using simulations with MATLAB software. Based on the simulation data that has been obtained, it is found that the temperature can be stabilized at 25 ℃ by using the fuzzy logic control method. By using the 5x5 fuzzy control method, the temperature can reach 25℃ with a time of 0.389ms while with 7x7 fuzzy the temperature can stabilize at 25℃ with a time of 0.407ms. Based on the results of open loop test, the temperature will continue to decrease in the range of 21 ℃, this is because this test does not use fuzzy logic control so that the temperature can't be stable at 25 ℃.